Cerebral Venous Sinus Thrombosis Manifesting as a Recurrent Spontaneous Subdural Hematoma: A Case Report. (2020) - Alharshan, Reem; Qureshi, Hammad U.; AlHada, Abdullah; Shaikh, Muhammed; Khalil, Ayman
Highlights: Cerebral sinus venous thrombosis is a rare cause for a subdural hematoma and should be considered in the differential diagnosis of such cases. Neuroradiological imaging has a valuable role in diagnosing and follow-up of patients. Management of subdural hematoma secondary to venous sinus thrombosis could be challenging due to the controversy in using anticoagulation medications. Abstract: Background: Diagnosing cerebral sinus venous thrombosis (CSVT) manifested as a spontaneous subdural hematoma (SDH) is challenging due to variability of its clinical features. The neuroradiological investigation is crucial to confirm the diagnosis. The management of SDH secondary to CVST is controversial and not well established. Case description: We present a case of an adult man with Down's syndrome who underwent a left-sided craniotomy and evacuation of spontaneous subdural hematoma. Post-surgery magnetic resonance venography (MRV) revealed venous sinus thrombosis in the right transverse sinus with loss of flow signal. He was started on Apixaban two weeks post-surgery. Three months later, the patient re-presented with recurrence of the SDH. His anticoagulation was discontinued, and he underwent craniotomy reopening and evacuation of the recurrent hematoma. The patient returned to his baseline following this procedure. The patient was followed up in the out-patient clinic regularly. Interval brain MRI and MRV performed at six months showed further resolution of the thrombosis of the right sigmoid sinus with restoration of the venous flow. Conclusion: The management of SDH complicating CVST remains controversial due to the rarity of its presentation and the hazards associated with the use of anticoagulation.